Cover Image. Issue 8 (4th July 2022) - Kobayashi, Kenya; Ikeda, Atsuo; Matsumoto, Yoshifumi; Matsumura, Satoko; Omura, Go; Eguchi, Kohtaro; Sakai, Azusa; Ito, Akiko; Matsumoto, Fumihiko; Yoshimoto, Seiichi
Abstract : The cover image is based on the Education Surgical technique for superselective neck dissection under local anesthesia in recurrent head and neck cancer by Kenya Kobayashi et al., https://doi.org/10.1002/hed.27071 .